1998
DOI: 10.1103/physrevlett.80.3280
|View full text |Cite
|
Sign up to set email alerts
|

Growth Mechanism and Cross-Sectional Structure of Tetrahedral Amorphous Carbon Thin Films

Abstract: Spatially resolved electron energy loss spectroscopy is used to characterize the cross-sectional structure of highly tetrahedral amorphous carbon films, particularly concentrating on the sp 2 bonded surface layer. The surface layer is shown to be due to subsurface conversion from sp 2 to sp 3 bonding at the depth of carbon ion implantation during film growth. The thickness of the surface layer is used as a measure of the ion penetration depth, varying from 0.4 6 0.2 nm for 35 eV ions to 1.3 6 0.3 nm for 320 eV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
71
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(85 citation statements)
references
References 18 publications
(22 reference statements)
14
71
0
Order By: Relevance
“…[28][29][30] This sub-plantation process continues throughout the period of ta-C film deposition leading to compressive stress in the ta-C films in the range of 2-8 GPa 11,30 and a few angstrom thick sp 2 layer at the very top when deposition process is terminated. 11,[28][29][30] It has also been shown that the resistivity of SWCNT bundles changes when subjected to pressure and there is a sharp increase in the resistivity with the increase in pressure. 31 Thus, a working hypothesis could be formed that the evolving stress in the ta-C film is responsible for the changes in the resistance of the SWCNTN.…”
Section: B Evaporated Carbon Coated Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…[28][29][30] This sub-plantation process continues throughout the period of ta-C film deposition leading to compressive stress in the ta-C films in the range of 2-8 GPa 11,30 and a few angstrom thick sp 2 layer at the very top when deposition process is terminated. 11,[28][29][30] It has also been shown that the resistivity of SWCNT bundles changes when subjected to pressure and there is a sharp increase in the resistivity with the increase in pressure. 31 Thus, a working hypothesis could be formed that the evolving stress in the ta-C film is responsible for the changes in the resistance of the SWCNTN.…”
Section: B Evaporated Carbon Coated Samplesmentioning
confidence: 99%
“…The other factor which must be considered is the stress induced during the process of ta-C film formation. The formation of ta-C film from energetic ions has been explained by the sub-plantation model [28][29][30] wherein the Cþ ion penetrates a few angstrom below the substrate surface, and due to the increase in pressure/density, sp 3 bond formation is promoted. [28][29][30] This sub-plantation process continues throughout the period of ta-C film deposition leading to compressive stress in the ta-C films in the range of 2-8 GPa 11,30 and a few angstrom thick sp 2 layer at the very top when deposition process is terminated.…”
Section: B Evaporated Carbon Coated Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these attributes, DLC films are widely used for surface protection in cutting tools [2;3], magnetic storage discs [4], biomedical devices [5][6], antireflection coatings, and optical sensors [7]. Various mechanisms have been proposed in order to describe the formation of sp 3 bonds in DLC films [1,[8][9][10][11]; among them, the most accepted view for amorphous carbon films without significant hydrogen incorporation is that the sp 3 formation is triggered by subsurface densification generated by subplantation of energetic deposited species [1,[9][10][11]. In plasma assisted physical vapor deposition (PVD) techniques, the energetic species are predominantly inert gas (Ar + ) and target-based (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive efforts in making diamond-like amorphous carbon [16][17][18] and tetrahedral amorphous carbon [19][20][21][22][23][24] using subplantation of incident ions have produced thin films with exceptional properties of high hardness, inertness, transparency and wide-bandgap semiconductivity for applications such as protective coatings for optical, electronic, mechanical, and biomedical components. However, these carbon films have less than 88% sp 3 -bonding, often contain a significant amount of hydrogenated carbon and nanocrystalline diamond, and are significantly different from a fully sp 3 -bonded bulk amorphous material.…”
mentioning
confidence: 99%